2005
DOI: 10.1191/1352458505ms1205oa
|View full text |Cite
|
Sign up to set email alerts
|

Relapse rates and enhancing lesions in a phase II trial of natalizumab in multiple sclerosis

Abstract: There was a lower proportion of subjects with an on-study relapse in natalizumab-treated patients, particularly in those with a more active disease at study entry. Larger ongoing phase III studies will allow more definitive investigation of these preliminary subgroup findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…In the large Phase III trial studying combination therapy, the SENTINEL Trial, 21 patients were at somewhat later disease duration and had breakthrough activity while on IFN␤-1a therapy. In the Phase II trial, which included both RRMS and SPMS patients, 15,17 the disability at baseline and disease duration were considerably greater (mean EDSS ϭ 4.2-4.4; mean duration ϭ 10.2-13.1 years). All three of these natalizumab trials 15,17,[20][21][22] showed a significant benefit of treatment (as evaluated by a relative-risk comparison) on both clinical and MRI measures of disease activity defined earlier (tables 2 and 3), with MRI activity being suppressed by 80 -90% and clinical activity being reduced by 50 -70%.…”
Section: Description Of the Analytic Processmentioning
confidence: 99%
See 3 more Smart Citations
“…In the large Phase III trial studying combination therapy, the SENTINEL Trial, 21 patients were at somewhat later disease duration and had breakthrough activity while on IFN␤-1a therapy. In the Phase II trial, which included both RRMS and SPMS patients, 15,17 the disability at baseline and disease duration were considerably greater (mean EDSS ϭ 4.2-4.4; mean duration ϭ 10.2-13.1 years). All three of these natalizumab trials 15,17,[20][21][22] showed a significant benefit of treatment (as evaluated by a relative-risk comparison) on both clinical and MRI measures of disease activity defined earlier (tables 2 and 3), with MRI activity being suppressed by 80 -90% and clinical activity being reduced by 50 -70%.…”
Section: Description Of the Analytic Processmentioning
confidence: 99%
“…In the Phase II trial, which included both RRMS and SPMS patients, 15,17 the disability at baseline and disease duration were considerably greater (mean EDSS ϭ 4.2-4.4; mean duration ϭ 10.2-13.1 years). All three of these natalizumab trials 15,17,[20][21][22] showed a significant benefit of treatment (as evaluated by a relative-risk comparison) on both clinical and MRI measures of disease activity defined earlier (tables 2 and 3), with MRI activity being suppressed by 80 -90% and clinical activity being reduced by 50 -70%. In both of the 2-year Class I trials in which disease severity was measured, [20][21][22] there was a significant benefit of treatment on both clinical and MRI measures of disease severity defined earlier (tables 2 and 3).…”
Section: Description Of the Analytic Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from a randomized, double-blind, placebo-controlled, phase II study in 343 patients with RRMS showed that the highest dose of firategrast resulted in a significantly lower cumulative number of new gadolinium-enhancing lesions (49 %) [105]. However, experience from the phase II natalizumab trial reported a 92 % reduction [106], pointing towards a lower efficacy of firategrast than expected. Furthermore, none of the doses of firategrast resulted in a significantly lower frequency of relapses compared with placebo.…”
Section: Therapies Aiming At T-lymphocyte Migration [Anti-α4β Integrimentioning
confidence: 92%